The Role of Laboratory Professionals in Preventing Contamination of Food by Antimicrobial-Resistant Microorganisms (AMRMs) - O.O. Oludairo; J. O. Aiyedun; B.B. Oludairo; M. P. Oludairo; F.E. Fabiyi; A.A. Imam (Journal of Applied Veterinary Sciences, 2025)
Antimicrobial-resistant-microorganism (AMRM)-infected or contaminated food that leads to livestock losses and disease/death in humans is estimated to put 31 million people at risk of food insecurity in Nigeria by the last quarter of 2024.  This study aimed to explicate the roles of food-industry stakeholders/laboratorians in preventing food contamination and animal/human infection by AMRMs. The objectives were to determine what food/food system, food security, and stakeholders in the food industry are; investigate the occurrence of AMRM in food; and elucidate preventive measures to be implemented to avoid AMRM in food. A structured questionnaire was administered to stakeholders and baseline information from published literature/established international standards was used to achieve this purpose. The majority (88%) of the respondents were from the Veterinary Teaching Hospital, University of Ilorin; all (100%) participants from the laboratories stated they knew the meaning of food security, while 56% of respondents that were ≤25 years old stated that AMRM could contaminate food. Only 52% of university-educated respondents agreed they were stakeholders in the food industry while 60% were veterinarians/medical practitioners. Reported contamination of food by AMRMs from harvest to consumption, especially in low/middle-income countries (LMICs) like Nigeria was by antimicrobial-resistant Staphylococcus spp., Bacillus spp., Proteus spp., Salmonella spp., and Clostridium spp. This was largely enhanced by the unrestricted use of antimicrobial agents in food animals, especially as growth promoters, leading to the production of unwholesome food, outbreaks of zoonoses, loss of livestock, and human diseases that were foodborne. Compulsory antimicrobial susceptibility tests should be done for isolates from food/food products to determine their suitability for use and the presence of AMRM. The diffusion method of antimicrobial susceptibility testing (AST) should strictly follow the International Standard Organization (ISO) protocol, which includes using pure colonies, overnight culture of 0.5 McFarland turbidity, and interpreting zones of inhibition using the Clinical and Laboratory Standard Institute (CLSI) recommended breakpoints. Only certified safe and wholesome food/food products should be passed to the public for consumption. Universities and researchers should carry out more extension work outside establishments’ walls to disseminate research results in food-AMRM.